The evaluation of structural properties of reinforced concrete building designed according to pre-modern code considering seismic performance. (December 2015) - Ergün, Ali; Kıraç, Nevzat; Başaran, Veli
Abstract: In this study, the structural properties of reinforced concrete buildings designed according to pre-modern code (1998 Turkish Earthquake Code (TEC)) are investigated considering seismic performance. These kinds of buildings reflect the majority of the existing building stock. As part of this study, 20 reinforced concrete buildings' projects are achieved from different municipalities. These reinforced concrete buildings designed and applied pre-modern code (1998 TEC) have different number of stories. Reinforced concrete projects are re-calculated by protecting structural systems' properties of available buildings in two ways: firstly by calculating in terms of only buildings' vertical load effects not considering the seismic loads; secondly by calculating the under seismic loads according to 1975 Turkish Earthquake Code which was built on the date of these buildings' designed. The obtained analysis results of reinforced concrete buildings re-designed according to different load cases are compared with existing application projects. In this way, it is tried to be defined which load cases have been used in the analysis of designed buildings before 1998 according to the realization rate. Furthermore, it is found that the relations between the internal forces occurring in the existing structural elements under seismic loads defined according to 2007 Turkish Earthquake Code and the shear and moment capacities of existing structural elements. Highlights: The structural properties of RC buildings designed according to 1998 Turkish Earthquake Code are investigated. RC projects are re-calculated by protecting structural systems' properties of available buildings. It is found that the relations between the internal forces occurring in the existing structural elements